2022
DOI: 10.2147/ccid.s267217
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Tralokinumab in the Treatment of Atopic Dermatitis: A Review on the Emerging Clinical Data

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease that greatly impacts patient quality of life. Type 2 cytokine interleukin (IL)-13 is integral to the pathogenesis of AD. Tralokinumab is a fully human IgG4 monoclonal antibody that specifically targets IL-13, preventing downstream signaling of inflammatory pathways that may contribute to AD. Tralokinumab was US Food and Drug administration (FDA) recently approved for the treatment of moderate to severe AD on December 28, 2021. In our review, we will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
3
5
0
Order By: Relevance
“…21,26,27 Despite differences in dosing regimens and treatment duration, the proportion of patients achieving EASI-75, vIGA 0 or 1, and P-NRS-4 were overall similar to proportions from previous studies with biologics that block IL-13 function. 9,10 Treatment with cendakimab, an anti-IL-13 monoclonal antibody that blocks the interaction of IL-13 with IL-13Rα1 and IL-13Rα2, also decreased inflammatory biomarkers in this study. Specifically, cendakimab decreased levels of key inflammatory and remodeling biomarkers (eotaxin-3, periostin, and MMP-12) during 16 weeks of treatment.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…21,26,27 Despite differences in dosing regimens and treatment duration, the proportion of patients achieving EASI-75, vIGA 0 or 1, and P-NRS-4 were overall similar to proportions from previous studies with biologics that block IL-13 function. 9,10 Treatment with cendakimab, an anti-IL-13 monoclonal antibody that blocks the interaction of IL-13 with IL-13Rα1 and IL-13Rα2, also decreased inflammatory biomarkers in this study. Specifically, cendakimab decreased levels of key inflammatory and remodeling biomarkers (eotaxin-3, periostin, and MMP-12) during 16 weeks of treatment.…”
Section: Discussionsupporting
confidence: 51%
“…Safety findings from this study were similar to findings in other phase 2 studies of biologic agents targeting IL-4 and IL-13 for treating moderate to severe AD. 9,10,22,23,26,29 TEAEs were similar across treatment groups, with most events reported as mild or moderate. Rates of serious AEs were similar across groups.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The reduction in the frequency of application and the total consumption (measured in grams) of topical corticosteroids as an adjuvant to new systemic therapies would be interesting. Tralokinumab is currently the only drug that has recorded this aspect, showing a reduction in both variables [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the therapeutic potential of tralokinumab in the treatment of AD published by Kelly et al [133] revealed improvements in disease severity measures (including IGA scores and EASI-75 scores), and in quality of life (including pruritus scores; sleep interference scores; DLQI; SCORing Atopic Dermatitis, SCORAD; Patient Oriented Eczema Measure; and The Short Form 36 Health Survey).…”
Section: Tralokinumab-an Il-13 Inhibitormentioning
confidence: 99%